"AMA DE CASA" - A HIDDEN FORM OF ENTREPRENEURIAL SUCCESS? RE-CHALLENGING GENDERED ROLES. (1st April 2010) - Wehrli, Angelica
Abstract : Achieving equality between women and men was declared one of the main targets of the Cuban Socialist revolution in 1961. Disparities related to gender such as unequal opportunities and access to the labour market, sexism, or sexual harassment were together identified as a product of capitalism and therefore had to be expunged. During Cuba's pre-1959 capitalist past, inequalities related to gender prevailed in a variety of forms, but it was presumed that they would disappear with the building of a 'new' socialist society. Today, 50 years later, the question arises as to if and how these ambitious goals have been reached. In this article I explore challenges women are facing, grounded on qualitative field research and thereby include qualitative field research material as well as statistics. In this context I will shed light on the re-evolving practice of labelling oneself as a 'housewife'. Furthermore, I will analyse whether this signifies a re-identification with 'traditional' role divisions between men and women or rather refers to a hidden - and not yet discussed academically - form of entrepreneurial success. To conclude, I will investigate the possible implications of these changes for both individuals and Cuban society as a whole.